DynamoDB cookbook : over 90 hands-on recipes for designing Internet-scalable web and mobile applications with Amazon DynamoDB /: over 90 hands-on recipes for designing Internet-scalable web and mobile applications with Amazon DynamoDB. (2015) - Deshpande, Tanmay
No abstract available